Induction of NAD (P)H: Quinone reductase 1 (QR1) and antioxidant activities in vitro of 'Toranja Burarama' (Citrus maxima [Burm.] Merr.). (12th July 2018) - da Silva, Elysiane S.; Oliveira, Bruno G.; Pereira, Ana Claudia H.; Pimentel, Elisângela F.; Pezzuto, John M.; Lenz, Dominik; Kondratyuk, Tamara P.; Andrade, Tadeu U.; Fronza, Marcio; Scherer, Rodrigo; Maia, June F.; Romão, Wanderson; et al.
Abstract : Toranja 'Burarama', Citrus maxima (Burm.) Merr. ( Citrus grandis ), is a new citrus discovered in the State of Espírito Santo, Brazil. As several varieties of citrus are known to possess antioxidant and cancer chemopreventive properties, the aim of the study was to evaluate in vitro if this Toranja possess these properties. The antioxidant activity, the potential to induce quinone reductase 1, and the influence on cell viability were measured. ESI(‐)FT‐ICR MS analysis was also performed and identified flavonoids, coumarins, and fatty acids in the extract. The ethyl acetate and methanolic extracts of the peels presented the highest antioxidant activity in vitro by DPPH (IC50  = 298.3 ± 2.6 μg/ml and 303.8 ± 0.4 μg/ml), ABTS assay (IC50  = 298.2 ± 6.4 μg/ml and 296.4 ± 2.5 μg/ml), and FRAP (IC50  = 234.6 ± 1.8 μg/ml and 398.1 ± 3.8 μg/ml). The ethyl acetate extract of the peel induced quinone reductase 1 activity in Hepa1c1c7 cells, indicating that C. maxima exhibited cancer chemopreventive properties.